2018
DOI: 10.18632/oncotarget.24869
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging with positron emission tomography and computed tomography (PET/CT) for selecting first-line targeted treatment in metastatic breast cancer: a cost-effectiveness study

Abstract: Our aim was to evaluate the potential cost-effectiveness of PET/CT with FES and 89Zr-trastuzumab compared to pathology to select first-line targeted treatment in metastatic breast cancer (MBC) patients with non-rapidly progressive disease. A previously published and validated model was extended and adapted for this analysis. Two alternative scenarios were compared. In the care as usual pathway first-line targeted treatment of MBC patients was assigned on the basis of pathology results, while in the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Two computer simulation studies described the impact of [ 18 F]-FES-PET/CT on health-related measurements, such as life years gained (LYG), ICER, and total costs (Table 1) [55,56]. One study selected first-line treatment in MBC patients based on biopsy results or [ 18 F]-FES-PET/CT imaging findings and showed higher diagnostic and treatment costs in the PET/CT imaging group [56].…”
Section: Clinical Utilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Two computer simulation studies described the impact of [ 18 F]-FES-PET/CT on health-related measurements, such as life years gained (LYG), ICER, and total costs (Table 1) [55,56]. One study selected first-line treatment in MBC patients based on biopsy results or [ 18 F]-FES-PET/CT imaging findings and showed higher diagnostic and treatment costs in the PET/CT imaging group [56].…”
Section: Clinical Utilitymentioning
confidence: 99%
“…Two computer simulation studies described the impact of [ 18 F]-FES-PET/CT on health-related measurements, such as life years gained (LYG), ICER, and total costs (Table 1) [55,56]. One study selected first-line treatment in MBC patients based on biopsy results or [ 18 F]-FES-PET/CT imaging findings and showed higher diagnostic and treatment costs in the PET/CT imaging group [56]. A second study determined the number of avoided biopsies to assess MBC after the introduction of [ 18 F]-FES-PET/CT and showed that the number of biopsies (39 ± 9%) was lower in the [ 18 F]-FES-PET/CT imaging group [55].…”
Section: Clinical Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor metastasis is considered a major mortality cause in breast cancer patients (31). To investigate whether SNHG1 regulates breast cancer cell migration, wound healing assays were performed to detect cell migration following SNHG1 knockdown.…”
Section: Snhg1 Knockdown Inhibits Cell Migration Of Breast Cancer Cellsmentioning
confidence: 99%
“…Breast cancer also represents a great model for this type of approach [12,13]. Indeed, in this pathology, 18F-fluoroestradiol (FES) PET has been validated as an accurate method for providing information on estrogen receptor (ER) status of tumor lesions to determine need for endocrine therapy [14,15,16,17].…”
Section: Inter- and Intra-patient Tumor Heterogeneity Exploration mentioning
confidence: 99%